(untitled) (Agroindustria, Sociedad y Ambiente, 2024)
The research was carried out in the plant biotechnology laboratory of the Meta agroindustrial center, located in the city of Villavicencio. The main objective was to evaluate in vitro morphogenesis in Phalaenopsis leaf explants, to examine the morphogenic capacity of the leaves. For the analysis, a mixture of substrates with additions of phytohormones was carried out as follows: the Murashige and Skoog culture medium, 2,4 dichlorophenoxyacetic acid (2,4-D) (1, 5, 10 [mg/l) was used. ]) and Benzylaminopurine (BAP) (0.1, 0.5 and 1 [mg/l]). The culture medium without the addition of stimulants was used as a comparison standard or control. The media were then autoclaved. The leaves were evaluated for differences in levels of contamination, phenolization, necrosis, and oxidation. This allowed us to observe that the level of uncontaminated leaves (HNC) was 89%. Phenolization did not occur in a greater proportion in treatment 2 (T2), which allowed the control of Phalaenopsis senescence. Oxidation occurred at 72% in treatment 2, to verify. Finally, necrosis was reported in 55% of Phalaenopsis leaves under this variable. The application of the correct proportion of biostimulants has a considerable influence on the propagation of Phalaenopsis.